Hydrocracking of Calophyllum inophyllum Oil Employing Co and/or Mo Supported on γ-Al2O3 for Biofuel Production - Wega Trisunaryanti; Triyono Triyono; Mohammad Ali Ghoni; Dyah Ayu Fatmawati; Puspa Nindro Mahayuwati; Endah Suarsih (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Cobalt and/or Molybdenum based catalysts were simply dispersed on γ-Al2O3 through wet impregnation. The set of prepared monometallic and bimetallic catalysts of aCoO/γ-Al2O3, aMoO/γ-Al2O3, aCoOaMoO/γ-Al2O3, and bCoObMoO/γ-Al2O3 were investigated and evaluated in the hydrocracking of Calophyllum inophyllum (CIO) which is not a food crop as well as rich in unsaturated fatty acid that potential to be converted into biofuel. Out of the prepared catalysts, aCoOaMoO/γ-Al2O3 with total metal content, acidity, and specific surface area of 13.62 wt%, 5.01 mmol.g-1, and 107.67 m2.g-1, respectively, showed the best catalytic performance. The high metal loading of aCoOaMoO/γ-Al2O3is favorable by producing 65.56 wt% liquid fraction through carbocation formation mechanism. It was selective to produce 8.61 wt% gasoline and 5.01 wt% diesel. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).